(untitled) (Heritage, 2023)
Since the time when women cultivated the land, in order to feed their families, to this day, when numerous opportunities offered by modern life can help them fight for their financial independence, very little has changed. 107 female respondents who took part in this research stated that the primary economic activity they are engaged in is still agriculture. Fear of failure, as well as social prejudices that are increasingly highlighted as formidable and major barriers which, despite emphasizing the importance of the concept of gender equality, directly affect women’s decisions about starting their own business, did not deter them from expressing their great determination and willingness to get involved in the process of switching to organic production and thus start their own business in the foreseeable future. Bearing in mind the aforementioned, it is evident that, under difficult business conditions, adequate financial and moral support from all possible relevant sources is necessary to maintain and support the entrepreneurial spirit of women in the province of Kosovo and Metohija.